Perceptions on the implementation of 5-S Practice on selected Japanese manufacturing companies in FCIE, Dasmariñas, Cavite : an assessment. [computer file] - Saquilayan, Corazon A. (2008)
ABSTRACT see Upload (MT MBA 61 2008)